Blood and Blood: Anti‐retroviral Therapy, Masculinity, and Redemption among Adolescent Boys in the Eastern Cape Province of South Africa. (14th January 2022) - Gittings, Lesley; Colvin, Christopher J.; Hodes, Rebecca
Abstract: Adolescents living with perinatally acquired HIV are among the first generation in South Africa to grow up with anti‐retroviral therapy and democratic freedoms. In this article, we explore the biosocial lives of adolescent boys and young men living with HIV in the Eastern Cape Province of South Africa. We conducted qualitative research with 36 adolescent boys and young men in 2016‒2018, including life history narratives, semi‐structured interviews, and analysis of health facility files. [masculinity, South Africa, HIV, adolescence]